ANALISIS KESIAPAN EKOSISTEM HALAL VALUE CHAIN INDONESIA DALAM MENDUKUNG DAYA SAING PRODUK HALAL LOKAL DI PASAR GLOBAL - Maulana, Nurfadilah; Wardah Jafar (Universitas Mathla’ul Anwar Banten, 2025)
This study aims to analyze the readiness level of the halal value chain (HVC) ecosystem in Indonesia to support the competitiveness of local halal products in the global market. The research method used is a descriptive qualitative approach based on literature review with secondary data from various national and international institutions such as BPJPH, KNEKS, DinarStandard, and UNCTAD. The results indicate that the readiness of the Indonesian HVC ecosystem is still partial, with glaring weaknesses in halal logistics, technology adoption, Islamic financing, and compliance with global halal standards. Meanwhile, the regulatory and certification sectors have shown progress, but are not yet optimal in reaching halal MSMEs. This study recommends strengthening cross-sector synergies, accelerating the digitalization of the halal system, reforming halal financing, and harmonizing national halal standards with international standards to enhance the competitiveness of the Indonesian halal industry.